2011
DOI: 10.1007/s12020-011-9436-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between serum levels of thyroid hormones and serum concentrations of asymmetric dimethylarginine (ADMA) and N-terminal-pro-B-type natriuretic peptide (NT-proBNP) in patients with Graves’ disease

Abstract: Endothelial dysfunction as well as abnormal thyroid hormone levels may be responsible for increased cardiovascular risk in Graves' disease (GD). Asymmetric dimethylarginine (ADMA) and N-terminal-pro-B-type natriuretic peptide (NT-proBNP) are new markers of endothelial and myocardial dysfunction, respectively. The purpose of this study was to investigate the relationship among the serum levels of ADMA, NT-proBNP, and thyroid hormones in GD patients. This was a cross-sectional investigation conducted in a univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
5
8
1
3
Order By: Relevance
“…Mean ADMA level was the highest among the hyperthyroid group. Gu et al showed that ADMA increases in patients with Graves (15). The result of the present study was in concordance with the results of the all of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
“…Mean ADMA level was the highest among the hyperthyroid group. Gu et al showed that ADMA increases in patients with Graves (15). The result of the present study was in concordance with the results of the all of the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
“…However, it must be stated that this study lacked a control group [34]. The positive association of increased NT-pro-BNP, as well as asymmetric dimethylarginine (a marker of endothelial dysfunction), with free thyroid hormone levels and heart rate has also been confirmed by others [35]. Another study has been conducted in patients with GD and overt hyperthyroidism in which AS was estimated as pulse pressure (that is systolic-diastolic BP)/stroke volume, by using echocardiographic methodology.…”
Section: Hyperthyroidism and Arterial Stiff-nesssupporting
confidence: 51%
“…The plasma concentration of these methylarginines in renal transplant patients correlates inversely with the renal expression of alanine-glyoxylate aminotransferase 2 (26). ADMA is substantially raised in hyperthyroidism (27) and critical illness (28), that is, two conditions characterized by high sympathetic activity (29,30) and enhanced protein degradation (31,32), suggesting that reduced sympathetic activity after renal denervation may attenuate the release of these compounds from methylated proteins. Whether the sympathetic system regulates methylarginines by interfering with the synthesis or the degradation of these compounds remains to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%